Cultivating Sustainability: A Cultural Linguistic Study of Minangkabau Environmental Proverbs - Handoko, Handoko; Kaur, Sheena; Su Kia, Lau (Jurnal Arbitrer, 2024)
The research aims to examine the connection between language, culture, and environment by analyzing the representation of nature in Minangkabau proverbs and its cultural implications and cognitive awareness in traditional Minangkabau society. It is a descriptive study that analyzes meaning and cultural representation through a cultural linguistics approach. The research used 287 proverbs from various written Minangkabau resources, including tambo and books containing Minangkabau proverbs. The study focuses on three sustainability pillars: social, environmental, and economic. The research findings show that Minangkabau proverbs frequently utilize symbolism of nature and the environment to describe and reflect cultural values and rules of Minangkabau customs. The natural representations reveal the close relationship between the Minangkabau people and nature and the cognitive awareness and shared knowledge passed down from generation to generation. The results of this study highlight the need for further research on Minangkabau proverbs to explore cultural values and wisdom that can support program sustainability. Hence, preserving and promoting cultural heritage values are crucial for sustainable development, as it can contribute to socio-economic development and create new values for future generations.